Peran citra merek pada pengalaman menggunakan uang elektronik - Saputri, Ika Puji; Randyantini, Vely; Nurcahyo, Bagus (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to examine the effect of brand image on customer experience in the use of electronic money. Where for the purposes of testing the hypothesis using the dimensions of customer experience sense, feel, think, act and relate. Respondents in this study were users of electronic money issued by Bank Mandiri and BCA as many as 110 respondents with a minimum use of 3 months. Collecting data using a questionnaire and this study in assessing the hypothesis using path analysis. Based on the empirical evidence obtained, the results of this study are known that the brand image variable has a positive effect on customer experience in using electronic money, especially the experience of feeling the ease of refilling, use for payment transactions and the breadth of the reach of electronic money.